Challenges and strategies for sustaining youth-friendly health services — a qualitative study from the perspective of professionals at youth clinics in northern Sweden. Issue 1 (December 2016) - Thomée, Suzanne; Malm, Desiré; Christianson, Monica; Hurtig, Anna-Karin; Wiklund, Maria; Waenerlund, Anna-Karin; Goicolea, Isabel
Abstract Background Youth-friendly health-care services — those that are accessible, acceptable, equitable, appropriate and effective for different youth subpopulations – are beneficial for youth health, but not easy to implement and sustain. Sweden is among the few countries where youth-friendly health-care services have been integrated within the public health system and sustained for a long time. This study explores the challenges and strategies in providing sustainable youth-friendly health-care services, from the perspective of professionals working in youth clinics in northern Sweden. Methods Eleven semi-structured interviews with various health-care professionals working in youth clinics in northern Sweden were conducted. The interviews were transcribed verbatim, and analysed using thematic analysis in relation to the World Health Organization domains of youth friendliness. Results Four themes emerged from the analysis of the data: 1) 'Meeting youths on their own terms – the key to ensuring a holistic and youth-centred care' was related to the acceptability and appropriateness of the services; 2) 'Organizational challenges and strategies in keeping professionals' expertise on youth updated' referred to the domain of effectiveness; 3) 'Youth clinics are accessible for those who know and can reach them' was related to the domains of accessibility and equity, and 4) 'The challenge of combining strong directions and flexibility in diverse local realities' focused on the struggle to sustain the youth clinics organization and their goals within the broader health system. Conclusions Professionals working in youth clinics are perceived as motivated, interested and knowledgeable about youth, and the clinics ensure confidentiality and a youth-centred and holistic approach. Challenges remain, especially in terms of ensuring equitable access to different youth subpopulations, improving monitoring routines and ensuring training and competence for all professionals, independently of the location and characteristics of the clinic. Youth clinics are perceived as an indisputable part of the Swedish health system, but organizational challenges are also pointed out in terms of weak clear directives and leadership, heavy workload, local/regional diversity and unequitable distribution of resources.